Frail geriatric patients with acute calculous cholecystitis: Operative versus nonoperative management?. Issue 1 (18th July 2021) - Asmar, Samer; Bible, Letitia; Obaid, Omar; Anand, Tanya; Chehab, Mohamad; Ditillo, Michael; Castanon, Lourdes; Nelson, Adam; Joseph, Bellal
Abstract : Supplemental digital content is available in the text. Abstract : INTRODUCTION: Nonoperative management of acute calculous cholecystitis (ACC) in the frail geriatric population is underexplored. The aim of our study was to examine long-term outcomes of frail geriatric patients with ACC treated with cholecystectomy compared with initial nonoperative management. METHODS: We conducted a 2017 analysis of the Nationwide Readmissions Database and included frail geriatric (≥65 years) patients with ACC. Frailty was assessed using the five-factor modified frailty index. Patients were stratified into those undergoing cholecystectomy at index admission (operative management [OP]) versus those managed with nonoperative intervention (nonoperative management [NOP]). The NOP group was further subdivided into those who received antibiotics only and those who received percutaneous drainage. Primary outcomes were procedure-related complications in the OP group and 6-month failure of NOP (readmission with cholecystitis). Secondary outcomes were mortality and overall hospital length of stay. RESULTS: A total of 53, 412 geriatric patients with ACC were identified, 51.0% of whom were frail: 16, 791 (61.6%) in OP group and 10, 472 (38.4%) in NOP group (3, 256 had percutaneous drainage, 7, 216 received antibiotics only). Patients were comparable in age (76 ± 7 vs. 77 ± 8 years; p = 0.082) and modified frailty index (0.47 vs. 0.48; p = 0.132). Procedure-related complications in the OP group were 9.3%, and 6-month failure of NOP was 18.9%. Median time to failure of NOP management was 36 days (range, 12–78 days). Mortality was higher in the frail NOP group (5.2 vs. 3.2%; p < 0.001). The NOP group had more days of hospitalization (8 [4–15] vs. 5 [3–10]; p < 0.001). Both receiving antibiotics only (odds ratio, 1.6 [1.3–2.0]; p < 0.001) and receiving percutaneous drainage (odds ratio, 1.9 [1.7–2.2]; p < 0.001) were independently associated with increased mortality. CONCLUSION: One in five patients failed NOP and subsequently had complicated hospital stays. Nonoperative management of frail elderly ACC patients may be associated with significant morbidity and mortality. LEVEL OF EVIDENCE: Therapeutic, level IV.